2007
DOI: 10.1097/gme.0b013e3180305299
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of equol status in the effects of isoflavone on bone and fat mass in postmenopausal Japanese women

Abstract: Our data suggest that the preventive effects of isoflavones on bone loss and fat accumulation in early postmenopausal women depend on an individual's equol-producing capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 42 publications
2
80
1
3
Order By: Relevance
“…Equol also has a 100-fold higher affinity for oestrogen receptors and a higher bioavailability than daidzein and glycitein [35]. Although many studies have reported the role of equolproducing status as an effect-modifier in the association between the intake of soybean products and endocrine-related diseases, the mechanism for this is not clear [36,37]. Because of equol's low affinity for serum protein, high affinity for the oestrogen receptor and high antioxidant activity, the clinical effectiveness of soy isoflavones may be a function of the ability to biotransform soy isoflavones to the more potent oestrogenic metabolite equol, which may enhance the action of soy isoflavones [38].…”
Section: Discussionmentioning
confidence: 95%
“…Equol also has a 100-fold higher affinity for oestrogen receptors and a higher bioavailability than daidzein and glycitein [35]. Although many studies have reported the role of equolproducing status as an effect-modifier in the association between the intake of soybean products and endocrine-related diseases, the mechanism for this is not clear [36,37]. Because of equol's low affinity for serum protein, high affinity for the oestrogen receptor and high antioxidant activity, the clinical effectiveness of soy isoflavones may be a function of the ability to biotransform soy isoflavones to the more potent oestrogenic metabolite equol, which may enhance the action of soy isoflavones [38].…”
Section: Discussionmentioning
confidence: 95%
“…93 Equol possesses more estrogen-like proteins than DAN and plays a crucial role in the soy phytoestrogen efficacy. 91 Studies showed that compared with GEN, equol had better improved biomechanical and histomorphometric properties in OVX rats; equol (103.8%) and GEN (96.8%) reached similar treatment levels compared with estrogen in the analysis of vertebral body compression strength. 94 Moreover, several studies also demonstrated that long-term equol consumption (10 lg/g bw/day intake for 3 months) provided better bone-sparing effects in OVX rats, 95 while dietary equol (400 mg/kg intake for 6 weeks) decreased weight gain and uterotropic activity.…”
Section: Study Populationmentioning
confidence: 99%
“…Equol is the metabolite of DAN, which has shown to be more potent compared with purified DAN. 91 Equol is not produced in all healthy humans as only 30-60% of the population can produce equol, and production is higher among Asians and vegetarians. 92 Equol and O-desmethylangolensin (ODMA) producers were defined as those people with detectable equol (87.5 ng/mL or 362 nM) and ODMA (87.5 ng/mL, or 399 nM) in their urine.…”
Section: Study Populationmentioning
confidence: 99%
“…Evidence has suggested that the clinical efficacy of isoflavones in humans depends on their ability to produce equol, a microbial metabolite of daidzein and is more estrogenic than daidzein. 46,47 As only 30-50% of the Chinese population can produce equol after soyfood ingestion, equol-producing status may be an important modifier of the effects of isoflavones. Compared with the earlier studies, this study has a relatively large sample.…”
Section: Soy Protein and Body Composition Z-m Liu Et Almentioning
confidence: 99%